C2O and Frontyard: hacking the archives to design community spaces in Surabaya and Sydney. Issue 8 (24th November 2019) - Bacon, Luke; Azali, Kathleen; Crosby, Alexandra Lara; Forster, Benjamin
Abstract : Purpose: The purpose of this study is to identify shared themes and concerns of two local and critical archives by comparing their design and day-to-day practice. Design/methodology/approach: The action research has drawn on the experience of collaboration between a Sydney-based community space (Frontyard) and the Surabaya-based co-working community (C2O) over one year. Each space houses a small physical library of books, which is the focus of this analysis. Findings: Hacking has emerged as a key value of both archives. A hacking approach has shaped the design of each space and the organisation each archive. Hacking frames the analysis of each collection in this study. Practical implications: Pragmatic and political understanding of such archives have implications for better quality and more authentic exchange between the communities that make use of these libraries in Indonesia and Australia. Originality/value: While some work on local critical archives has been done in Indonesia and Australia, no research to date has made specific comparisons with the aim of sharing knowledge. Because these archives are often temporary and ephemeral, documenting the work that goes into them, and their practitioners' perspectives, is urgent, making possible shared knowledge that can inform the ways communities make decisions about their own heritage.